2021
DOI: 10.3389/fnins.2021.717572
|View full text |Cite
|
Sign up to set email alerts
|

Listening in the Moment: How Bilingualism Interacts With Task Demands to Shape Active Listening

Abstract: While there is evidence for bilingual enhancements of inhibitory control and auditory processing, two processes that are fundamental to daily communication, it is not known how bilinguals utilize these cognitive and sensory enhancements during real-world listening. To test our hypothesis that bilinguals engage their enhanced cognitive and sensory processing in real-world listening situations, bilinguals and monolinguals performed a selective attention task involving competing talkers, a common demand of everyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…Enhancements in FFRs because of bilingualism were reflected in different aspects of the neural response. For example, some studies showed greater consistency and stability of FFRs among bilinguals compared to monolinguals [ 25 , 28 , 33 ] and among bilinguals who are more proficient in the language [ 25 ] and have more years of bilingual experience [ 27 ]. Other studies showed that exposure to a second language induces earlier neural latencies [ 20 ], more pronounced and robust FFRs [ 22 , 23 ], and a larger representation of the fundamental frequency (F0) component [ 24 , 26 , 27 ], which is used to recognize and track speech, and serves as an important cue for speech perception in challenging listening conditions [ 26 , 34 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhancements in FFRs because of bilingualism were reflected in different aspects of the neural response. For example, some studies showed greater consistency and stability of FFRs among bilinguals compared to monolinguals [ 25 , 28 , 33 ] and among bilinguals who are more proficient in the language [ 25 ] and have more years of bilingual experience [ 27 ]. Other studies showed that exposure to a second language induces earlier neural latencies [ 20 ], more pronounced and robust FFRs [ 22 , 23 ], and a larger representation of the fundamental frequency (F0) component [ 24 , 26 , 27 ], which is used to recognize and track speech, and serves as an important cue for speech perception in challenging listening conditions [ 26 , 34 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…We used the Prolific online research platform to recruit the participants. Considering how monolingual and bilingual individuals perform differently in competitive talking scenarios on the neural and cognitive levels [ 36 ], participants were recruited from monolingual English-speaking people, currently residing in the United States of America, who were screened by Prolific not to have any hearing difficulties and had no understanding of the Russian language. Participants were asked to wear headphones during the task and attend the task in a quiet room.…”
Section: Methodsmentioning
confidence: 99%